PLANNING OPTIMIZATION PLANNING IRIGATION AREA OF SOLOK SUMATERA WEST REGENCY - Acep Hidayat; Deri Ferdina (NAROTAMA UNIVERSITY, 2019)
Solok Regency irrigation network planning which has an area of irrigation land of 3738 ha. The main canals are spread in several areas, namely 43 Irrigation Channels, 17 Dams, 7 Reservoirs and 2 lakes which are still functioning in Solok Regency. The poverty rate in Solok Regency is still quite high, reaching 27,487%. The data includes secondary data on 10-year rainfall data from KayuAro, Bayur Maritime Bay Methodology, Padang Panjang Geophysics and 10-year climatology from KayuAro Climatology Station. The calculation method used is the intensity of theissen rainfall method, Evapotranspiration of the modified Penman method, the reliable discharge of the DR.FJ Mock method, the cropping pattern, and the need for irrigation water. The most efficient and optimal planting pattern obtained is PADI-PADI-CORN with large irrigation water requirements in tertiary plots (NFR tertiary plots) ranging from 0 - 1,546 ltr / sec / ha with a maximum of 1,546 ltr / sec / ha in September II, whereas Irrigation water demand in the intake (DR intake) ranges from 0 to 2,378 ltr sec / ha with a maximum of 2,378 ltr / sec / ha in September II.The mainstay discharge available in the Pauh Tinggi Irrigation Network Planning is very abundant with the mainstay discharge (Q80) for irrigation, the maximum mainstay discharge (Q80) occurs in April I with 10.482 ltr / sec / ha and minimum in December II with 3,930 ltr / sec / ha. Based on the mainstay discharge results above it can be stated that the water balance / water balance between the mainstay discharge Q80 and the need for irrigation water experienced a large surplus